The moral world of the first Christians - Meeks, Wayne A. 1932- (Library of early Christianity ;, 1986)
This volume in the Library of Early Christianity examines the ethics and morality of the earliest Christians.The Library of Early Christianity is a series of eight outstanding books exploring the Jewish and Greco-Roman contexts in which the New Testament...